2022
DOI: 10.1037/pha0000412
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a brief assessment of opioid demand among post-discharge trauma care patients.

Abstract: Opioid misuse and opioid-related death are a growing public health concern. One population of interest is recent trauma and/or surgery patients, who are at increased risk of developing an opioid use disorder (OUD). Although a variety of assessments have been developed to screen for risk of opioid misuse, each has limitations and prediction needs improvement. One promising measure is drug demand, a behavioral economic measure assessing drug consumption at different price points. In the current proposal, we asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 62 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…Strickland et al (2019) found that opioid demand indices, like intensity, predict opioid use disorder, and Pickover et al (2016) found that demand for opioid pain relievers was significantly associated with, and predicted, measures of pain‐reliever use and pain reliever use disorder symptoms. Abuse liability of prescription opioids has also been assessed in multiple studies, which have found that opioid demand is associated with morphine amounts received during hospital stays (Yoon et al, 2020) and is a sensitive measure of abuse potential that can distinguish between different opioid formulations (Schwartz et al, 2019). However, no prior study has shown a relationship between HPT measures of demand for opioids in participants at different points in recovery from substance‐use disorder.…”
mentioning
confidence: 99%
“…Strickland et al (2019) found that opioid demand indices, like intensity, predict opioid use disorder, and Pickover et al (2016) found that demand for opioid pain relievers was significantly associated with, and predicted, measures of pain‐reliever use and pain reliever use disorder symptoms. Abuse liability of prescription opioids has also been assessed in multiple studies, which have found that opioid demand is associated with morphine amounts received during hospital stays (Yoon et al, 2020) and is a sensitive measure of abuse potential that can distinguish between different opioid formulations (Schwartz et al, 2019). However, no prior study has shown a relationship between HPT measures of demand for opioids in participants at different points in recovery from substance‐use disorder.…”
mentioning
confidence: 99%
“…While these are limitations, results of the present study showed similar effects of relevant covariates (e.g., FTND) on demand measures of studies that did not use crowdsourcing (e.g., Chase et al, 2013; Schwartz, Silberberg, et al, 2021). Additionally, there appears to be good correspondence between real and hypothetical demand tasks (e.g., Wilson et al, 2016), and purchase tasks are predictive of real treatment outcomes (González-Roz et al, 2020; Schwartz, Silberberg, et al, 2021; Secades-Villa et al, 2016; Yoon et al, 2020). It is possible that participants could have responded to experimenter expectations rather than the experimental manipulations (i.e., demand characteristics/good subject effect; Orne, 1962).…”
Section: Discussionmentioning
confidence: 94%
“…For example, a meta-analysis of cigarette demand studies (González-Roz et al, 2019) found that the Fagerström Test for Nicotine Dependence (FTND; Heatherton et al, 1991) is positively correlated with intensity (i.e., base consumption increased) and negatively correlated with sensitivity to price. Other studies have found that intensity (González-Roz et al, 2020; Yoon et al, 2020) and sensitivity to price (González-Roz et al, 2020; Schwartz, Blank, et al, 2021; Secades-Villa et al, 2016) assessed via purchase tasks correspond with likelihood of drug relapse and abstinence. A recent meta-analysis also found that purchase tasks are also sensitive to manipulations such as interventions or hypothetical contexts (Acuff et al, 2020).…”
Section: Determining Drug Valuementioning
confidence: 97%
“…The current findings systematically extend the growing number of brief drug assessments to a novel drug of abuse, cocaine. Previous brief demand assessments have been developed for alcohol (Amlung et al, 2015;Owens et al, 2015;Merrill and Aston, 2020), cigarettes (Athamneh et al, 2019;Murphy et al, 2019) and opioids (Yoon, Suchting, Kessler, et al, 2020). In all these studies, indices of demand were found to be significantly associated with clinically relevant measures of drug use, with Q 0-brief and O max-brief typically showing the most robust effects.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the analysis of data derived from purchasing tasks can be relatively complex, requiring appropriate software to model demand curves using nonlinear regression (Hursh and Silberberg, 2008;Koffarnus et al, 2015;Kaplan et al, 2019), which may prohibit its use in some applied settings. More recently, brief assessments for drug demand have been developed for alcohol (Amlung et al, 2015;Owens et al, 2015;Merrill and Aston, 2020), cigarettes (Athamneh et al, 2019;Murphy et al, 2019) and opioids (Yoon, Suchting, Kessler, et al, 2020). These brief assessments typically consist of questions that provide a proxy index for three important indices of demand (i.e.…”
Section: Introductionmentioning
confidence: 99%